2015
DOI: 10.3233/jad-142646
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Function Impairment in Alzheimer’s Disease

Abstract: AD could involve impairments in the vestibular control of balance. The VS test is useful for assessing the tendency to fall in AD. Impairment of VS in AD might arise from cerebral vestibular cortex impairment rather than comorbid peripheral vestibular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…5, 7 Nakamagoe et al 7 previously reported impaired caloric responses in 12 AD patients compared with younger controls, although there was no difference relative to age-matched controls. Further, in a study of postural sway among individuals with cognitive impairment, Leandri et al 30 observed progressively increased anterior-posterior sway in control, MCI and AD patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5, 7 Nakamagoe et al 7 previously reported impaired caloric responses in 12 AD patients compared with younger controls, although there was no difference relative to age-matched controls. Further, in a study of postural sway among individuals with cognitive impairment, Leandri et al 30 observed progressively increased anterior-posterior sway in control, MCI and AD patients.…”
Section: Discussionmentioning
confidence: 96%
“…5, 7 One study found that individuals with AD had impaired caloric responses relative to younger, but not age-matched controls. 7 Patients with AD were also observed to have poorer postural control – a proxy measure of vestibular function and other sensory and motor inputs– compared to normal older individuals. 30 Another study found that individuals with different degrees of cognitive impairment had abnormal sacculocollic reflexes.…”
mentioning
confidence: 99%
“…16 Vestibular dysfunction may influence multiple biological processes, including bone integrity, 17 sense of self, 18 and even cognition in space; 19 therefore, it is difficult to distinguish cognitive dysfunctions due to vestibular effects from neurodegenerative diseases on Earth and in space.…”
Section: Differential Diagnosis Of Cognitive Dysfunctionmentioning
confidence: 99%
“…It has long been believed that the cerebellum uses neural circuits in the vestibular system to process visual input information from the eye and then regulates the brain stem vestibular nucleus. However, several studies have contended that the cerebral cortex may be a key player in the neural circuits in the vestibular system [ 1 , 2 , 3 , 4 , 5 ]. Previous animal experiments have demonstrated that multiple vestibular cortex areas are scattered over the parietal and temporal lobes [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that Alzheimer's disease-related pathology in the cerebral cortex can cause impairment of vestibular function which, in turn, leads to impaired visual control [ 5 ]. Taking into account the above-mentioned findings, the present study proposes a hypothesis about a system in which the cerebral cortex uses visual information to control vestibular neural circuits in Alzheimer's disease patients.…”
Section: Introductionmentioning
confidence: 99%